Job Crafting Mediation on Self Efficacy and Burnout at PT PLN Indonesia Power - Krisloana Kendali; Liza Mumtazah Damarwulan (International Journal of Economics and Management Research, 2024)
An imbalance in workload and employee readiness for demands at work has the potential to cause burnout. This research adds job crafting as a skill to reorganize work in the most appropriate way. The research aims to examine the influence of self-efficacy on burnout which is mediated by job crafting. The research method uses a path analysis approach, with the research object being 100 employees at PT PLN Indonesia Power. This research found that there is an influence of self-efficacy on job crafting and the influence of job crafting on burnout. Employees who have self-efficacy and are given good job crafting are less likely to experience burnout.